1993
DOI: 10.1042/bj2910933
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the inhibitory mechanism of serpins by analysing the interaction of trypsin and chymotrypsin with α2-antiplasmin

Abstract: Human alpha 2-antiplasmin (alpha 2-AP) has previously been shown to possess overlapping inhibitory sites for trypsin and chymotrypsin [Potempa, Shieh and Travis (1988) Science 241, 699-700]. Since this is currently unique among active-site-directed inhibitors of proteinases, and difficult to explain in terms of accepted inhibitory mechanisms, we re-examined the claim. Initial characterization of purified alpha 2-AP revealed an additional 12 residues preceding the published N-terminus, prompting us to revise th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 22 publications
1
52
0
Order By: Relevance
“…Partitioning between the inhibitor and substrate pathways is seen for the interaction of serpins with some chymotrypsin family members (Patston et al, 1991;Gettins et al, 1992;Cooperman et al, 1993;Enghild et al, 1993;Schechter et al, 1993). However, it is not usually as extreme as shown here with the subtilisins unless specific mutations are made in the serpin that cause it to favor the substrate pathway (see Hood et al, 1994, for example).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partitioning between the inhibitor and substrate pathways is seen for the interaction of serpins with some chymotrypsin family members (Patston et al, 1991;Gettins et al, 1992;Cooperman et al, 1993;Enghild et al, 1993;Schechter et al, 1993). However, it is not usually as extreme as shown here with the subtilisins unless specific mutations are made in the serpin that cause it to favor the substrate pathway (see Hood et al, 1994, for example).…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, cleavage outside the P I inhibitory site, but within the RSL, causes partitioning (Schechter et al, 1989;Enghild et al, 1993). For the interaction of subtilisins with a l P I , both appear to occur and there are two components of the partitioning.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin modulation of serpin reactivity by induced conformational change was interpreted to support a preequilibrium model [17], as was the temperature dependence of the cleavage of the reactive site loop of a2AP by trypsin and chymotrypsin [54]. Recent studies showed identical immunoreactivity to antibodies, raised against cleaved ATIII, of either partially denatured, protease-111 121…”
Section: Referencesmentioning
confidence: 99%
“…Non-covalent Bond of SCCA1 and Papain-Although an SDS-resistant complex between SCCA1 and papain was not detected, it would be possible that the covalent bond between these two proteins is unstable to SDS, like the complex between chymotrypsin and ␣ 2 -antiplasmin (21). To retain the native association between SCCA1 and papain, we employed a gelfiltration system.…”
Section: Expression and Purification Of Functional Scca1mentioning
confidence: 99%